Analisis Peran Pendidikan Inklusif untuk Membangun Moral dalam Keberagaman di Sekolah Dasar - Anisa, Nur; Prasetyo, Sigit (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Inclusive education not only guarantees access to learning for all children, but also becomes a strategic place to build moral values in diversity. A learning environment that combines regular and special needs students creates space for the growth of empathy, tolerance and mutual respect. This article aims to analyze the role of inclusive education in shaping students' morality and examine the challenges and strategies for its implementation in elementary schools. This study uses a literature study method by reviewing various literature, scientific articles, and related research results. The data analysis technique used is content analysis, which is carried out repeatedly to ensure accurate understanding and avoid misinformation. The results of the study show that inclusive education has a positive contribution to the formation of students' morals, but its implementation still faces obstacles such as limited teacher competence, minimal facilities, and an inflexible curriculum. To overcome this, strategies are needed in the form of teacher training, provision of appropriate educators, adaptation of learning methods, and support from families. With comprehensive support, inclusive education can be an effective means of shaping children's character and morality from an early age.Keywords - Elementary School, Inclusive Education, Morals.